ChemInform Abstract: Structural, Magnetic, Magneto‐Caloric and Moessbauer Spectral Study of Tb2Fe17 Compound Synthesized by Arc Melting. Issue 27 (16th June 2016) - Charfeddine, S.; Zehani, K.; Bessais, L.; Korchef, A.
Abstract: Hexagonal Tb2 Fe17 is prepared by repeated arc melting of the elements without further annealing.